Influence of entrepreneurial and marketing behavior on the income of the photocopying business of Palano Jaya Medan Helvetia - Khoiria Rizky Tanjung (Central Research Institute for Agriculture (CeRIA), 2022)
This study aims to determine the effect of entrepreneurial and marketing behavior on income on photocopies of Palano Jaya. This research was conducted at Palano Jaya Medan Helvetia. Where researchers want to see how much influence entrepreneurship has on income, how much influence marketing has on income, and how much influence entrepreneurial and marketing behavior has on income Palano Jaya Medan. The dependent variable is income, the independent variable is entrepreneurial behavior and marketing. This research method uses quantitative methods. The data used are primary data and secondary data. Primary data was obtained using a questionnaire method (questionnaire) on a sample of 80 entrepreneurs. The analysis tool used is Multiple Linear Regression with the help of the SPSS 20.0 program. The results showed that all independent variables had a significant effect on Palano Jaya's income. The coefficient of determination is 0.649, which means that Palano Jaya's income can be explained by the entrepreneurial and marketing behavior variable factors of 64.9%. While the remaining 35.1% of Palano Jaya's income is explained by other variables not included in the analysis model in this study.